Factors secreted from high glucose treated endothelial cells impair expansion and differentiation of human skeletal muscle satellite cells. (1st October 2019) - Kargl, Christopher K.; Nie, Yaohui; Evans, Sheelagh; Stout, Julianne; Shannahan, Jonathan H.; Kuang, Shihuan; Gavin, Timothy P.
Abstract : Key points: Cellular communication occurs between endothelial cells and skeletal muscle satellite cells and is mitogenic for both cell types under normal conditions. Skeletal muscle atrophy and endothelial cell dysfunction occur in tandem in cardiovascular disease, type II diabetes and ageing. The present study investigated how induction of endothelial cell dysfunction via high glucose treatment impacts growth and differentiation of human skeletal muscle satellite cells in vitro . Secreted factors from high glucose treated endothelial cells impaired satellite cell expansion and differentiation via decreased proliferation and dysregulation of p38 mitogen‐activated protein kinase in satellite cells committed to myogenesis. These findings highlight a novel potential role for endothelial cells in the development and pathology of skeletal muscle atrophy, which is common in patients with endothelial dysfunction related pathologies. Abstract: Cross‐talk between endothelial cells (ECs) and skeletal muscle satellite cells (MuSC) has been identified as an important regulator of cellular functions in both cell types. In healthy conditions, EC secreted factors promote MuSC growth and differentiation. Endothelial and satellite cell dysfunction occur in tandem in many disease states; however, no data exist examining the impact of dysfunctional EC signalling on satellite cells. Therefore, the present study aimed to evaluate the effect that factors secreted from high glucose (HG) treated ECs have on the growth and differentiation of human satellite cells (HMuSC) using a conditioned medium (CM) cell culture model. Satellite cells were isolated from human skeletal muscle and grown in CM from normal or HG treated human umbilical vein ECs (HUVECs). Satellite cells grown in CM from HG treated HUVECs reduced growth (25%), differentiation (25%) and myonuclear fusion (35%). These responses were associated with increased superoxide (50%) and inflammatory cytokines (25–50%) in HG treated HUVECs and HG‐CM. Decreased expansion of HG‐CM treated HMuSCs was driven by a decrease in proliferation. Impaired gene expression and protein content of myogenic differentiation factors were preceded by decreased phosphorylation of p38 mitogen‐activated protein kinase in HMuSC treated with CM from HG treated HUVECs. The results obtained in the present study are the first to show that factors secreted from HG treated ECs cause impairments in human muscle satellite cell growth and differentiation in vitro, highlighting endothelial cell health and secretion as a potential target for treating vascular disease‐associated skeletal muscle dysfunction. Key points: Cellular communication occurs between endothelial cells and skeletal muscle satellite cells and is mitogenic for both cell types under normal conditions. Skeletal muscle atrophy and endothelial cell dysfunction occur in tandem in cardiovascular disease, type II diabetes and ageing. The present study investigated how induction of endothelial cell dysfunction via high glucose treatment impacts growth and differentiation of human skeletal muscle satellite cells in vitro . Secreted factors from high glucose treated endothelial cells impaired satellite cell expansion and differentiation via decreased proliferation and dysregulation of p38 mitogen‐activated protein kinase in satellite cells committed to myogenesis. These findings highlight a novel potential role for endothelial cells in the development and pathology of skeletal muscle atrophy, which is common in patients with endothelial dysfunction related pathologies.